Overconfidence, Investment Experience, and Herding Behavior: The Role of Financial Literacy in Nepal’s Stock Market (The Lumbini Journal of Business and Economics, 2025)
Purpose: This study investigates how overconfidence and past investing experience influence individual investors’ herding behavior on the Nepal Stock Exchange. Additionally, it looks into how financial literacy affects these connections, focusing on how it can encourage logical decision-making when behavioral biases are present.Methods: Data from 384 individual investors was analyzed using a cross-sectional and quantitative research design. A stratified random sampling technique was used to choose the participants, and structured survey questionnaires were used to gather the data. Partial Least Squares (PLS) were used to analyze measurement and structural equation models.Results: The analysis demonstrates that herding behavior among investors is significantly influenced by overconfidence and past investment experience. Financial literacy is a critical moderating factor that can either exacerbate or mitigate the effects of these cognitive biases.Conclusion: The study emphasizes how crucial financial literacy is for encouraging self-directed investing choices and reducing the negative consequences of behavioral biases. These findings extend existing behavioral finance theories by illustrating how financial literacy can serve as a corrective mechanism against irrational market behavior, paving the way for future research on the long-term impact of financial education programs and the role of cultural factors in shaping investor psychology. These results underscore the necessity of economic education and policy measures to enhance rational investment behavior in Nepal’s equity market.